PENGARUH JENIS MUSIK TERHADAP KECEMASAN PENGEMUDI - Sari, Yeni Kurnia; Wijayanto, Hendra; K., Naomie Srie (FSTPT Indonesia, 2015)
The driver is the person who drives a motor vehicle on the street who has had a driver's license (UU no.22 of 2009). In driving, the driver demanded highly concentrated and is always eager to deal with various situations on the road. This causes a disparate impact to the driver while driving the anxiety. In addition to the internal factors, there are several external factors that also cause anxiety while driving. Listening to music while driving is one that affects the driver's level of anxiety. The type of music you listen to is different and has different influences, rock types raise the level of anxiety experienced by the driver during ksperiment done, whereas the type of classical music and dance have actually lowered the anxiety level.